Pelatihan Manajemen Organisasi Dan Service Excellence Dalam Meningkatkan Kinerja Pegawai Kesekretariatan GAPENSI Se-Jawa Barat - Rr. Rachmawati; Terra Saptina Maulani (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Infrastructure development is the mainstay of the Government of Indonesia to improve the nation's economy. Infrastructure development must continue because it is one of the drivers of the national economy. A forum for gathering and developing companies in the field of construction implementing business is GAPENSI (National Construction Implementing Association) consisting of 34 (thirty-four) Regional Management Boards or Badan Pengurus Daerah (BPD) spread throughout Indonesia. One of the BPDs is the BPD of West Java Province which currently houses 27 (twenty-seven) secretariats spread across cities and regencies throughout West Java. In the continuity of the organization, of course, human resources are needed in this case the employees who manage the secretariat. Realizing that the function of the secretariat is as a center for administrative activities, communication, and organizational information, as well as being a driving force for the implementation of all work activities both internally and externally, in improving services it is necessary to have the support of all employees. as a stakeholder who provides services, it is necessary to have service excellence training. Providing good service, will not only have an impact on member satisfaction but can build a good organizational culture. Not only in terms of service, but the staff's ability also needs to be improved so that organizational performance can increase with good administrative management. Whether or not the journey of an organization, or whether or not the organization's goals are achieved, depends on the organization's management.